SEISMIC REFLECTION DATA ANALYSIS AND THE TECTONIC SETTING OF MANSURIYA OIL FIELD - Almashaekhy, Dhiya aldin (Iraqi Journal of Science, 2024)
People who work on the analysis of seismic refection data usually use highly sophisticated software particularly when it is related to oil exploration data. In this article it will be shown how simple software like Reflex (2008) can deal with the seismic data with efficiency not less than professional software. Data of two seismic lines that were executed at Mansouriayah Oil field were used. After the filtering and processing reverse faults were detected. These faults isolate the top of Mansouriayah fold to form a gas reservoir. These types of reverse faults, which appear at the south western limb of the Mansouriayah fold, are also noticed for most High Folded Zone mountains. They are Gravity collapse faults that usually develop on both sides of the fold. They were developed following thin skin detachment movements in the basement rocks.